Smart Communities and Digital Participation: Rethinking Grassroots Empowerment in the Digital Era - Mulyaningsih Mulyaningsih; Carlos Fernandez; Isabel Martinez (Yayasan Adra Karima Hubbi, 2026)
Background. The integration of digital infrastructure within the smart city paradigm has frequently prioritized technocratic efficiency over authentic civic engagement, leading to a critical need to re-evaluate how technology serves local communities. Purpose. This research explores the dynamics of digital participation to determine whether current smart initiatives truly foster grassroots empowerment or merely digitize existing institutional hierarchies. Method. A qualitative case study design was employed, utilizing semi-structured interviews and digital ethnography to analyze interaction patterns within community-led and municipal platforms. Results. Findings reveal a persistent agency paradox, where high technological access does not equate to political influence; instead, meaningful empowerment is driven by decentralized platform architectures and high levels of digital literacy. Results indicate that communities utilizing peer-to-peer networks achieve significantly higher policy impact compared to those restricted to top-down administrative applications. Conclusion. The study concludes that rethinking empowerment requires a shift from transactional service delivery to Algorithmic Agency, where citizens possess the autonomy to manage and contest community data. True smartness must be redefined through the lens of democratic inclusivity and technical self-sufficiency. This research provides a foundational framework for urban planners to design more equitable digital ecosystems that prioritize human-centric empowerment over purely operational metrics.